Kinetic versus thermodynamic control of mutational effects on protein homeostasis: A perspective from computational modeling and experiment. (24th May 2019) - Pobre, Kristine Faye R.; Powers, David L.; Ghosh, Kingshuk; Gierasch, Lila M.; Powers, Evan T.
Abstract: The effect of mutations in individual proteins on protein homeostasis, or "proteostasis, " can in principle depend on the mutations' effects on the thermodynamics or kinetics of folding, or both. Here, we explore this issue using a computational model of in vivo protein folding that we call FoldEcoSlim. Our model predicts that kinetic versus thermodynamic control of mutational effects on proteostasis hinges on the relationship between how fast a protein's folding reaction reaches equilibrium and a critical time scale that characterizes the lifetime of a protein in its environment: for rapidly dividing bacteria, this time scale is that of cell division; for proteins that are produced in heterologous expression systems, this time scale is the amount of time before the protein is harvested; for proteins that are synthesized in and then exported from the eukaryotic endoplasmic reticulum, this time scale is that of protein secretion, and so forth. This prediction was validated experimentally by examining the expression yields of the wild type and several destabilized mutants of a model protein, the mouse ortholog of cellular retinoic acid‐binding protein 1.